Improving Benchmarks for Global Surgery: Nationwide Enumeration of Operations Performed in Ghana. Issue 2 (August 2018) - Gyedu, Adam; Stewart, Barclay; Gaskill, Cameron; Boakye, Godfred; Appiah-Denkyira, Ebenezer; Donkor, Peter; Maier, Ronald; Quansah, Robert; Mock, Charles
Abstract : Objective: To evaluate the operation rate in Ghana and characterize it by types of procedures and hospital level. Background: The Lancet Commission on Global Surgery recommended an annual rate of 5000 operations/100, 000 people as a benchmark at which low- and middle-income countries could achieve most of the population-wide benefits of surgery, but did not define procedure-type benchmarks. Methods: Data on operations performed from June 2014 to May 2015 were obtained from representative samples of 48 of 124 district-level (first-level) hospitals, 9 of 11 regional (referral) hospitals, and 3 of 5 tertiary hospitals, and scaled-up to nationwide estimates. Operations were categorized into those deemed as essential procedures (most cost-effective, highest population impact) by the World Bank's Disease Control Priorities Project versus other. Results: An estimated 232, 776 [95% uncertainty interval (95% UI) 178, 004 to 287, 549] operations were performed nationally. The annual rate of operations was 869 of 100, 000 (95% UI 664 to 1073). The rate fell well short of the benchmark. 77% of the estimated annual national surgical output was in the essential procedure category. Most operations (62%) were performed at district-level hospitals. Most district-level hospitals (54%) did not have fully trained surgeons, but nonetheless performed 36% of district-level hospital operations. Conclusion: The operation rate was short of the Lancet Commission benchmark, indicating large unmet need, although most operations were in the essential procedure category. Future global surgery benchmarking should consider both total numbers and priority levels. Most surgical care was delivered at district-level hospitals, many without fully trained surgeons. Benchmarking to improve surgical care needs to address both access deficiencies and hospital and provider level.